2020
DOI: 10.1080/02640414.2020.1786991
|View full text |Cite
|
Sign up to set email alerts
|

Developing a two-dimensional landscape model of opportunities for penetrative passing in association football – Stage I

Abstract: This study investigated a method for modeling a landscape of opportunities for penetrative passing completed on the ground by ball carriers in association football.Analysis of video footage of competitive, professional football performance was undertaken, identifying a sample (n=20) of attacking sub-phases of game play which ended in a penetrative pass being made between defenders to a receiver. Players' relative co-positioning during performance was modelled using bi-dimensional x and y coordinates of each pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
11
0
4
Order By: Relevance
“…Perhaps, the higher work rate preceding successful goal scoring opportunities discovered by Schulze et. al (2022) 2022elicits fatigue in defenders which not only impairs their motivation to intercept passes (Barte et al, 2020) but also decreases their ability to perform sprints needed to prevent penetrating passes (Passos et al, 2020).…”
Section: Changes In Pressure During Drs and Codsmentioning
confidence: 99%
“…Perhaps, the higher work rate preceding successful goal scoring opportunities discovered by Schulze et. al (2022) 2022elicits fatigue in defenders which not only impairs their motivation to intercept passes (Barte et al, 2020) but also decreases their ability to perform sprints needed to prevent penetrating passes (Passos et al, 2020).…”
Section: Changes In Pressure During Drs and Codsmentioning
confidence: 99%
“…For the players "in possession of the ball", the intention to play through shines a light on opportunities for playing penetrative passes in the landscape of shared affordances to pass and receive between the defenders. 43 But for the defenders, the shared affordances perceived would relate to opportunities for pass interception and the closing of spaces for opponents to play penetrative passes.…”
Section: Phase Twomentioning
confidence: 99%
“…Such results are aligned with previous findings on passing frequency of midfielders. It has been observed that midfielders preferentially explore affordances for passing opportunities to progress up field, through the defensive lines, seeking to play penetrative passes to attackers in space (Liu et al, 2016;Passos et al, 2020).…”
Section: Midfielders' Team Rolementioning
confidence: 99%
“…It has been observed that midfielders preferentially explore affordances for passing opportunities to progress up field, through the defensive lines, seeking to play penetrative passes to attackers in space. 27,28 In fact, midfielder players are usually the players with higher centrality of play (i.e., the players that receive and distribute more passes to other players) inside of the network of relations of a team, assuming the main responsibility to promote the flow of passes between different team sectors. 6 In line with our previous findings, midfielders revealed, in ball possession effectiveness, a lower number of shots at goal, compared to teams of defenders.…”
Section: Midfielders' Team Rolementioning
confidence: 99%